Implementation of the Papua Special Autonomy Policy to Improve the Welfare of the Indigenous Papuan Community in Papua Province - Timed Magayang; Muchlis Hamdi; Hyronimus Rowa; Mansyur Ahmad (International Journal of Economics Development Research (IJEDR), 2023)
This research analyzes the implementation of special autonomy policies to improve the welfare of indigenous Papuans in Papua Province. The Papua region is the region with the highest poverty rate among the 38 provinces in Indonesia, but the poverty rate in the region is still stagnant. Even though special autonomy has been implemented for 20 years with a transfer of APBN funds of 1.25% from 2001 to 2020 through Law No. 21 of 2001, and increased to 2.25% from 2021 to 2041 through Law No. 2 of 2021 concerning Special Autonomy for Papua, but the government has not succeeded in improving the welfare of the indigenous Papuan people due to inconsistencies, conflicts and less firm policies. This research uses a qualitative method with a descriptive analysis approach. Primary data collection techniques used include interviews, observation and documentation. The documents required by researchers include related laws and regulations, data archives from Papua regional government offices, and other relevant data. Based on research results, during the treatment of special autonomy in Papua it has not reduced the poverty rate and improved the welfare of indigenous Papuans for twenty years. Then the results of data analysis related to the implementation of the Papua special autonomy policy to improve the welfare of the people in Papua Province, are divided into two dimensions, namely: The "content" dimension includes aspects: interests affected, types of benefits, level of change, location of decision making, program implementation, and resource availability. The research suggestion is for political and power stakeholders in Indonesia that the implementation of Papua's special autonomy policy to improve the welfare of indigenous Papuans requires strict supervision, mutual trust, open dialogue, public consultation, and reducing top-down policies and implementing policies that bottom-up based.